Social Interaction Among Elementary School Children Who Are Victims Of Bullying - Fajrin, Syarifa Nur; A Kamaruddin, Syamsu; Torro, Supriadi (Journal of Research and Multidisciplinary, 2025)
This research is a qualitative study with a case study approach aimed at understanding the social life of children who are victims of bullying at Madrasah Ibtidaiyah Yaspi, Makassar. The research subjects included four students and one teacher at Madrasah Ibtidaiyah Yaspi, Makassar. Data collection techniques involved in-depth interviews and documentation. The study utilized the interactive analysis model by Miles and Huberman, which consists of data collection, data condensation, data verification, and conclusion drawing and testing. The findings revealed that the causes of bullying at Madrasah Ibtidaiyah Yaspi, Makassar, include misinterpretations of intent and communication methods, a lack of understanding of cultural expressions such as congratulations, emotional reactions from peers who feel disturbed, stigmas formed after incidents, and insufficient education on managing minor conflicts. The social life of children who are victims of bullying at Madrasah Ibtidaiyah Yaspi, Makassar, is characterized by dynamics of support and rejection. The handling of bullying at Madrasah Ibtidaiyah Yaspi, Makassar, tends to be reactive and unstructured. Although there are no specific programs or policies to systematically address bullying, teachers play an active role in mediating conflicts between students. Teachers' efforts to instill values such as respect, mutual assistance, and honesty serve as a foundation for fostering a positive school culture.